2020
DOI: 10.1097/mao.0000000000002417
|View full text |Cite
|
Sign up to set email alerts
|

Intratympanic Diltiazem-Chitosan Hydrogel as an Otoprotectant Against Cisplatin-Induced Ototoxicity in a Mouse Model

Abstract: Hypothesis:Local administration of the calcium-channel blocker (CCB), diltiazem, via intratympanic (IT) chitosan-glycerophosphate (CGP) hydrogel will protect against cisplatininduced ototoxicity.Background: Cisplatin induces calcium-mediated apoptosis of cochlear outer hair cells (OHCs). Previous work demonstrated otoprotection and reduced auditory brainstem response (ABR) threshold shifts in a cisplatin-induced ototoxicity mouse model treated with multiple doses of IT diltiazem given in solution. Here, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…In an epidemiologic study, women taking CCB medications were found to have, on average, 12 dB better hearing than those not on a CCB (43). In vitro and in vivo results revealed that CCB treatment is protective in cisplatin-induced ototoxicity (10)(11)(12). Based on the preclinical findings, L-Type calcium channel blockade could be a potential therapeutic target for SNHL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an epidemiologic study, women taking CCB medications were found to have, on average, 12 dB better hearing than those not on a CCB (43). In vitro and in vivo results revealed that CCB treatment is protective in cisplatin-induced ototoxicity (10)(11)(12). Based on the preclinical findings, L-Type calcium channel blockade could be a potential therapeutic target for SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro and in vivo results show that CCB treatment is protective in cisplatin-induced ototoxicity (10)(11)(12). In vivo mouse models revealed, following cisplatin injection, intratympanic diltiazem administration reduced click-evoked auditory brainstem response (ABR) threshold shifts compared with control, highlighting potential therapy for cisplatin-induced ototoxicity (11,12). Further, a clinical study showed that patients treated with a combination of nimodipine, and a steroid had improved recovery from idiopathic sudden sensorineural hearing loss compared with steroid use alone (13).…”
mentioning
confidence: 99%
“…OTO-104(poloxamer hydrogel containing dexamethasone) provides a sustained-exposure to dexamethasone and alleviates cisplatin-induced ototoxicity ( Fernandez et al., 2016 ). A Diltiazem (calcium-channel blocker)-loaded chitosan-glycerophosphate (CGP) hydrogel has been used as a vehicle to provide controlled and sustained delivery to the inner ear ( Naples et al., 2020 ). In addition, hydrogel itself can be cross-linked with functional reagents, such as genipin or STS, with potential therapeutic effect ( Videhult Pierre et al., 2019 ; Yuksel Aslier et al., 2019 ).…”
Section: Strategies To Combat Cisplatin-induced Ototoxicitymentioning
confidence: 99%
“…Unfortunately, cisplatin HL is difficult to reproduce in a mouse model, as important systemic toxicity generally arises before the onset of mild to moderate ototoxicity. Current mouse models to study ototoxic adverse effects of cisplatin consist of intraperitoneal (IP) cisplatin injection of a single high dose (e.g., Parham, 2011 ; Naples et al, 2020 ) or lower doses in a repeated fashion ( Breglio et al, 2017 ; Fernandez et al, 2019 ; DeBacker et al, 2020 ). However, in such models, strong toxicity and animal distress are observed, including important weight loss and ataxia, raising important and prohibitive ethical concerns.…”
Section: Introductionmentioning
confidence: 99%